A TFPI-1 peptide that induces degradation of bacterial nucleic acids, and inhibits bacterial and viral infection in half-smooth tongue sole, Cynoglossus semilaevis. Issue 60 (January 2017) - He, Shu-wen; Zhang, Jian; Li, Ning-qiu; Zhou, Shun; Yue, Bin; Zhang, Min
Abstract: Tissue factor pathway inhibitor 1 (TFPI-1) is a serine protease inhibitor that inhibits tissue factor (TF)-mediated coagulation. The C-terminal region of TFPI-1 could be cleaved off and proved to be antimicrobial against a broad-spectrum of microorganism. In a previous study, a C-terminal peptide, TC24 (with 24 amino acids), derived from tongue sole ( Cynoglossus semilaevis ) TFPI-1, was synthesized and found antibacterial against Micrococcus luteus . In the present study, the antibacterial spectrum and the action mode of TC24 was further examined, and its in vivo function was analyzed. Our results showed that TC24 also possesses bactericidal activity against Staphylococcus aureus and Vibrio vulnificus . During its interaction with the target bacterial cells, TC24 destroyed cell membrane integrity, penetrated into the cytoplasm, and induced degradation of genomic DNA and total RNA. In vivo study showed that administration of tongue sole with TC24 before bacterial and viral infection significantly reduced pathogen dissemination and replication in tissues. These results indicated that TC24 is a novel antimicrobial peptide against bacterial and viral pathogens, and that the observed effect of TC24 on bacterial RNA adds new insights to the action mechanism of fish antimicrobial peptides. Moreover, TC24 may play an important role in fighting pathogenic infection in aquaculture. Highlights: A tongue sole TFPI-1 peptide TC24 displayed bactericidal activity against Staphylococcus aureus and Vibrio vulnificus. TC24 could destroy cell membrane integrity, penetrated into the cytoplasm, and induced degradation of nucleic acids. TC24 could inhibit bacterial or viral invasion in tongue sole.